THE IMPACT OF WORK LIFE BALANCE AND JOB SATISFACTION ON EMPLOYEE ENGAGEMENT OF DPRD MINAHASA TENGGARA OFFICE - Logor, Grand; Tulung, Joy; Wangke, Shinta (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The impact of work life balance and job satisfaction on employee engagement of DPRD minahasa tenggara office. 56 samples were collected with questionnaire distributed to the respondent who work as employee so the author can analyz the work lofe balance and job satiscfaction on employee engagement on their work place . this research used quantitative method Data analysis used Multiple Linear Regression analysis method conducted by using SPSS 25 version software. The results show that Work Life Balance and Job Satisfaction have a negative and insignificant impact on Employee Engagement at the DPRD Minahasa Tenggara Office. This suggests that, contrary to expectations, neither a fulfilling work environment nor positive job-related factors significantly drive employee engagement in this setting. Instead, leadership and the reputation of the office's directors appear to play a more critical role in influencing employee engagement.   Keywords: Work Life Balance, Job Satisfaction, Employee Engagement